Methodology for Applying Modern Tools in the Process of Training Future Engineers for Secondary Special and Professional Educational Institutions - Pardaboev Abdurahim (Zien Journals, 2023)
This article describes the positive aspects of effective use of modern educational and didactic tools in the educational process, methods of achieving lesson efficiency. In conclusion, the modern generation of technology science textbooks should be aimed at teaching students to acquire knowledge independently and apply it to practical activities, and to develop positive skills, self-evaluation of their own knowledge. should cover the system. This article mentions the positive aspects of using modern educational and didactic tools in the educational process, and ways to achieve training effectiveness.
Keywords: didactics; electronic resources; e-book